Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Hoàng Tùng Nguyễn

1)2x+(-15)-9=-24

2)(x-34):20=-12

3)13-2x=-25-(31-25)

4)250:(x-5)=64-14

5)12:(x+5)=17+(-23)

6)62+64:(x-1)=32

7)3.(x+5)-x-11=24

14)-19+4.(2-x)+x=25

15)17-{-x+[-x-(-x)]}=-16

Nguyễn Lê Phước Thịnh
30 tháng 11 2022 lúc 21:34

1: =>2x-24=-24

=>2x=0

=>x=0

2: =>x-34=-240

=>x=-206

3: =>-2x+13=-25-31+25=-31

=>-2x=-44

=>x=22

4: =>x-5=5

=>x=10

14: =>8-4x+x-19=25

=>-3x-11=25

=>-3x=36

=>x=-12

Ngô Hải Nam
30 tháng 11 2022 lúc 21:43

1)2x+(-15)-9=-24

2x-15-9=-24

2x=-24+15+9

2x=0

x=0

2)(x-34):20=-12

x-34=-12.20

x-34=-240

x=-240+34

x=-206

3)13-2x=-25-(31-25)

13-2x=-25-31+25

-2x=-25-31+25-13

-2x=-44

x=-44:(-2)

x=22

4)250:(x-5)=64-14

250:(x-5)=50

x-5=250:50

x-5=5

x=5+5

x=10

5)12:(x+5)=17+(-23)

12:(x+5)=17-23

12:(x+5)=-6

x:5=12:(-6)

x:5=-2

x=-2x5

x=-10

6)62+64:(x-1)=32

64:(x-1)=32-36

64:(x-1)=-4

x-1=64:(-4)

x-1=-16

x=-16+1

x=-15

7)3.(x+5)-x-11=24

3x+15-x-11=24

3x-x=24-15+11

2x=20

x=20:2

x=10

14)-19+4.(2-x)+x=25

-19+8-4x+x=25

-4x+x=25+19-8

-3x=36

x=36:(-3)

x=-12

17-{-x+[-x-(-x)]}=-16

\(17-\left\{-x+\left[-x+x\right]\right\}=-16\\ 17-\left\{-x-x+x\right\}=-16\\ 17+x+x-x=-16\\ x=-16-17\\ x=-33\)


Các câu hỏi tương tự
Ánh Ngọc
Xem chi tiết
Hà Trần Hoàng Châu
Xem chi tiết
Nguyễn Quỳnh Anh
Xem chi tiết
Trần Nguyễn Xuân Khôi
Xem chi tiết
Trần Nguyễn Xuân Khôi
Xem chi tiết
Phượng Phạm
Xem chi tiết
trần minh tâm
Xem chi tiết
Phượng Phạm
Xem chi tiết
Nguyễn Thị Thu Hiền
Xem chi tiết
Trần Khánh Ngọc
Xem chi tiết